PSIKOEDUKASI MANAJEMEN STRESS PADA LANSIA DI WILAYAH PUSKESMAS RANGKAH, SURABAYA - Marsya Rezkita Dewi (Journal of Research and Measurement in Psychology, 2019)
This psychological intervention aims to increase the knowledge of stress management among Rossela elderly community in Puskesmas Rangkah area, Surabaya by giving the psychoeducation about stress management. Proposed sampling was used as a technique sampling with 11 elderly as sample. The stress level of Rossela elderly community measured by Stress Assessment Questionnaire (SAQ) and the knowledge of elderly stress management measured by pretest-posttest questionnaire made by researcher. The result of intervention show positive effect by giving psychoeducation about stress management to the Rossela elderly community which the knowledge increases before and after giving psychoeducation and the effect size category is average (0.72).